Situating Norbert Elias’ Power Differential in a Critical Exploration of Violence in Chilean Education - Bacquet, Gaston (Advances in Social Sciences Research Journal, 2022)
Once hailed as a poster boy for neoliberalism, or what Milton Friedman called “The Miracle of Chile”, Chile has undergone a myriad of social and political changes that since 2011 have resulted in increased polarization and violent clashes between the opposing parties. The apex of this violence was reached in 2019, where civilians were blinded, public buses and subway stations burned and businesses vandalized in a series of violent acts that continued for weeks. Between October and November 2019, the country also experienced large peaceful demonstrations demanding greater equality towards women, sexual minorities and migrants (Chile has seen a surge in migration over the last 5 years, with 1.5 million people immigrating from Haiti, Venezuela and Colombia). It is against this background that I began my research to investigate to what degree this direct, structural and cultural violence had spilled over into classrooms. My doctoral research, titled “Non-violence as a practice of equality: an exploration in Chilean higher education classrooms through participatory action research” sought to co-develop non-violent strategies to tackle violence in the way of exclusion, discrimination and any other manifestation within classroom settings. This paper will explore the application of Elias’ notion of power differentials in the perpetration of cultural violence and the experience of violence by Chilean minorities as documented in my own research. I am particularly inspired by Norbert Elias’ work “The established and the outsiders”. Discussions with my research participants, all trainee teachers at Chilean universities, revealed that at the core of the instances of violence found lies a power imbalance and a view of those “outsiders” (migrants, lower income students, LGBTQI+) as less worthy and valuable and therefore victims to a wide range of violent acts resulting in exclusion and discrimination.